The Development of Adolescent and Young Adult Participation Sort – Taiwanese Version. (18th April 2013) - Hsin‐Yen, Wang; Berg, Christine
Abstract: The purpose of this pilot research was to translate the Adolescent and Young Adult Participation Sort into Taiwanese (AYAPS‐T), an assessment tool measuring the activity participation and the self‐identified barriers of youth transitioning into adulthood. The study included five phases: translation, cultural adaptation, taking photographs, field testing for content validity and pilot testing of test–retest reliability. A literature review, expert review and translation with back‐translation were conducted for the initial activities. The activities were then edited on the basis of the feedback of 23Taiwanese youth for content validity. Test–retest reliability (intraclass correlation coefficient = 0.91) of the AYAPS‐T reported by 22 Taiwanese youth was high. With the activities designed to meet the developmental needs of young adults, the methodology of sorting photographs, the barrier list to identify possible obstacles and some psychometric properties established, the AYAPS‐T serves as a reliable and valid tool to identify engagement of young adults in their occupations. Because of the nature of a pilot study, results are limited by a small sample size and limited evidence of psychometric properties. Psychometric properties such as interrater reliability and internal consistency as well as construct validity and concurrent validity need to be tested on a larger sample size. Copyright © 2013 John Wiley & Sons, Ltd.